2016
DOI: 10.1089/omi.2016.0120
|View full text |Cite
|
Sign up to set email alerts
|

Rolling out Efavirenz for HIV Precision Medicine in Africa: Are We Ready for Pharmacovigilance and Tackling Neuropsychiatric Adverse Effects?

Abstract: The introduction of antiretroviral therapy (ART) led to huge reductions in human immunodeficiency virus (HIV)-related deaths, turning HIV-infection into a chronic condition. Attention is now turning to quality of life for patients on lifelong ART treatment, reflecting on the safety of antiretroviral drugs. In sub-Saharan Africa, efavirenz (EFV) forms the preferred first-line ART but adverse drug events have also been reported. We express our concern on EFV-based regimens being part of mass rollout programs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The CYP2B6 gene is highly polymorphic [ 215 ] and the CYP2B6 c.516 G>T variant appears to strongly predict the pharmacokinetics of Efavirenz [ 216 ]. That is, this 516G>T change, specifically in HIV-infected individuals of African-ethnicity, genetically predisposes these patients (“slow Efavirenz metabolizers”) to develop adverse CNS reactions with a frequency of 34–50% [ 215 , 217 ]. This has important consequences for the African continent as it may dramatically increase the burden of psychiatric illness in HIV-infected patients [ 217 , 218 ].…”
Section: Drug Metabolism/transporter Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CYP2B6 gene is highly polymorphic [ 215 ] and the CYP2B6 c.516 G>T variant appears to strongly predict the pharmacokinetics of Efavirenz [ 216 ]. That is, this 516G>T change, specifically in HIV-infected individuals of African-ethnicity, genetically predisposes these patients (“slow Efavirenz metabolizers”) to develop adverse CNS reactions with a frequency of 34–50% [ 215 , 217 ]. This has important consequences for the African continent as it may dramatically increase the burden of psychiatric illness in HIV-infected patients [ 217 , 218 ].…”
Section: Drug Metabolism/transporter Genesmentioning
confidence: 99%
“…That is, this 516G>T change, specifically in HIV-infected individuals of African-ethnicity, genetically predisposes these patients (“slow Efavirenz metabolizers”) to develop adverse CNS reactions with a frequency of 34–50% [ 215 , 217 ]. This has important consequences for the African continent as it may dramatically increase the burden of psychiatric illness in HIV-infected patients [ 217 , 218 ]. In those individuals, compared to 15–20% of Caucasian and Asian populations [ 213 , 219 ], CYP2B6 enzyme activity is reduced, impairing the metabolism of Efavirenz and increasing plasma levels of the drug [ 215 , 217 , 220 ].…”
Section: Drug Metabolism/transporter Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior work, we showed that besides polymorphisms in CYP450 , those in SULT and UGT also give rise to different serum levels of some drug metabolites than detected in wild-type carriers of the genes [ 1 ]. To date, most pharmacogenetic studies have examined Asian and Caucasian populations and although the pharmacogenetics of CYP450 genes has been explored in sub-Saharan countries, scarce data exist for African genetic variations in SULT and UGT [ 2 , 3 ].…”
Section: What We Already Knowmentioning
confidence: 99%
“…Genetic variants in CYP2B6, which have been found at higher frequency in several African populations, affect the metabolism of EFV, thus predisposing these populations to the adverse effects. This argues for pharmacogenetics testing of CYP2B6 to improve the precision of EFV dosing [9].…”
Section: Data For the African Contextmentioning
confidence: 99%